Examining role of professional development initiatives from the perspectives of Key Learning Area Coordinators and Subject Heads: A mediation analysis. (2021) - Keung, Chrysa; Cheung, Alan; Mak, Barley; Tam, Winnie
Highlights: Three types of PDIs in relation to the NSS implementation were identified. Teachers' curriculum orientation was significantly associated with two PDIs. Collaborative practice among teachers was positively associated with three PDIs. Three PDIs have exerted different mediating effects on student learning. Facilitating various PDIs in the support of teachers' curriculum change. Abstract: The purpose of this study is to examine the mediating role of Professional Development Initiatives (PDIs) in relation to the implementation of New Secondary School curriculum in Hong Kong and student learning. Data were collected from 414 Key Learning Area coordinators and subject heads who were responsible for managing curriculum of senior secondary education in 91 Hong Kong secondary schools. Results indicated that three types of PDI (i.e. curriculum planning, professional sharing and support for teachers) mediated the impact of teachers' collaborative practices on their conceptions of student learning. Whereas two PDIs have exerted mediating effect of teachers' curriculum orientation on student learning. Implications for facilitating teachers' curriculum implementation towards reform and sustaining various types of PDIs are discussed.